ОХУ-ын инновацын хөгжлийн стратеги: Агуулга болон хэрэгжүүлэх арга зам - Ж, Орхон (Journal of International Studies, 2011)
English title: Innovation Development Strategy of the Russian Federation: its content and implementation methods